New Biochemical Parameters That Can Be Used to Diagnose Patients with G6PD Deficiency - Dr. Saad M. Saeed; Mohammed R. Tuama; Prof. Dr. Nazar A. Naji (Open Academia, 2025)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an inherited enzyme deficiency that affects millions of people worldwide, particularly in certain regions with high prevalence. Although diagnosis of G6PD deficiency traditionally relies on biochemical assays such as the fluorescent spot test and enzymatic activity tests, there is growing interest in exploring novel biochemical parameters that can aid in the diagnosis of this condition. In this research we will take (90) sample from serum of glucose-6-phosphate dehydrogenase deficiency patients and control and we will determine level of the glucose-6-phosphate dehydrogenase, albumin, total protein, and other biochemical parameters such as liver function; Alanine transaminase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), Bilirubin and compared with new biochemical parameters such as myo-inositol oxidase, hepcidin and haptoglobin. At the end of this research. The results showed that there was a significant decrease (P <0.05) in the serum levels of G6PD in patient’s group when compared with control group. Also, there were a significant increase (P><0.05) in the serum levels of albumin, total protein, ALP, ALT, AST and total bilirubin in patients with (G6PD) deficiency groups when compared with control group. In addition, this research reveals strong positive correlation between some biochemical parameters that we were studied such as total protein with TSB, total protein with albumin, ALT with TSB and Albumin with TSB>
Keywords: deficiency; Biochemical Parameters; Serum Biomarkers